Der Beauftragte als Rechtsfigur. - Werner, Wibke (Duncker & Humblot, 2024)
Commissioners are found in both legal and, increasingly, non-legal areas. This paper analyses the role of Federal Government Commissioners and Federal Commissioners. It focuses on their tasks, powers, independence and organisational structures as well as the legal basis for their appointment. It also describes the problems for the democratic rule of law that result from the creation of the Commissioners. The main aim of this thesis is to find out whether the legal basis of the Commissioner should be reformed.